Effect of wheel–rail interface parameters on contact stability in explicit finite element analysis. (July 2018) - Ma, Yuewei; Markine, Valeri L; Mashal, Abdul Ahad; Ren, Mingfa
It is widely recognized that the accuracy of explicit finite element simulations is sensitive to the choice of interface parameters (i.e. contact stiffness/damping, mesh generation, etc.) and time step sizes. Yet, the effect of these interface parameters on the explicit finite element based solutions of wheel–rail interaction has not been discussed sufficiently in literature. In this paper, the relation between interface parameters and the accuracy of contact solutions is studied. It shows that the wrong choice of these parameters, such as too high/low contact stiffness, coarse mesh, or wrong combination of them, can negatively affect the solution of wheel–rail interactions which manifest in the amplification of contact forces and/or inaccurate contact responses (here called "contact instability"). The phenomena of "contact (in)stabilities" are studied using an explicit finite element model of a wheel rolling over a rail. The accuracy of contact solutions is assessed by analyzing the area of contact patches and the distribution of normal pressure. Also, the guidelines for selections of optimum interface parameters, which guarantee the contact stability and therefore provide an accurate solution, are proposed. The effectiveness of the selected interface parameters is demonstrated through a series of simulations. The results of these simulations are presented and discussed.